A new species of Piaroa (Schizomida: Hubbardiidae) from Venezuela, with taxonomic notes on the genus - M., Osvaldo Villarreal; de Armas, Luis F.; García, Luis Fernando (Zootaxa, 2014)
A new species belonging to the schizomid genus Piaroa Villarreal, Giupponi and Tourinho, 2008 is described from north-western Venezuela. A complementary description of Piaroa guipongai Villarreal and Garcia, 2012 is provided including SEM pictures of relevant structures of both sexes. A key for males of Piaroa and Colombiazomus Armas and Delgado-Santa, 2012 is included. The presence of Dm3 setae on Hubbardiidae is discussed.